Climate change and the human factor: Why does not everyone realize what is happening?. (28th June 2019) - Brenner, Ira
Abstract: The notion of standing on "solid ground" is most reassuring. However, it is a myth, because we now know that the surface of the earth is composed of tectonic plates that float and move. Similarly, the notion that our climate is stable and fixed is also a myth. We now know that we are living in a time of great flux, and as science tell us, we have a role its fate. Psychological defenses against the affects and anxieties associated with awareness of this progressive upheaval fuel the current sociopolitical debate about "climate change." Maladaptive attitudes, rooted in ignorance, fear, superstition, and religion, will be looked at from a developmental perspective and applied to large‐group psychology. Just as young children are incapable of realizing that their violent actions could actually hurt their mothers, many adults refuse to believe that their actions could actually hurt "Mother Earth." In addition, the possible role of transmitted ancestral memory of earlier global catastrophe is also taken into consideration. As such, it may be an unrecognized factor that may complicate large‐group responses to this most pressing problem.